2015
DOI: 10.3109/07357907.2015.1055757
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Differentially Expressed Proteins of Normal and Cancerous Human Colorectal Tissues by Liquid Chromatograph-Mass Spectrometer Based on iTRAQ Approach

Abstract: Liquid chromatograph-mass spectrometer (LC/MS) based labeled with isobaric mass tags for relative and absolute quantitation (iTRAQ) analyses were performed to identify differentially expressed proteins from normal and cancerous human colorectal tissues. Around 802 proteins were identified, 68 proteins of which were defined as differentially expressed proteins. Bioinformatics analysis indicated that these differentially expressed proteins correlated with several specific cellular processes and pathways which ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…Recent studies have shown that EHD2 could function as a tumor suppresser protein. 39 42 EHD2 overexpression was inversely associated with overall survival and EHD2 knockdown significantly enhanced breast cancer and esophageal squamous cell carcinoma (ESCC) cell migration, cell invasion and enhanced epithelial to mesenchymal transition (EMT). 39 , 40 In this study, we observed that dissociation of EHD2 from myoferlin in activated tumor cells (treated with IL-6) led to enhanced tumor cell motility and cancer stem cell phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that EHD2 could function as a tumor suppresser protein. 39 42 EHD2 overexpression was inversely associated with overall survival and EHD2 knockdown significantly enhanced breast cancer and esophageal squamous cell carcinoma (ESCC) cell migration, cell invasion and enhanced epithelial to mesenchymal transition (EMT). 39 , 40 In this study, we observed that dissociation of EHD2 from myoferlin in activated tumor cells (treated with IL-6) led to enhanced tumor cell motility and cancer stem cell phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…| 7 of 12 colorectal cancer through liquid chromatograph-mass spectrometer (LC/MS) based labeled with isobaric mass tags for relative and absolute quantitation (iTRAQ) analysis, including EHD2. 102 Studies have shown that EHD2 expression is decreased in CC tissues, which is associated with poor prognosis. 103 And the knockdown of EHD2…”
Section: Type Of Cancer Expression Actionsmentioning
confidence: 99%
“…Thus, there is a need to further investigate the molecular mechanisms of CC and identify new therapeutic targets to improve the survival rate for CC patients. Lv et al identified differentially expressed genes in colorectal cancer through liquid chromatograph‐mass spectrometer (LC/MS) based labeled with isobaric mass tags for relative and absolute quantitation (iTRAQ) analysis, including EHD2 102 . Studies have shown that EHD2 expression is decreased in CC tissues, which is associated with poor prognosis 103 .…”
Section: The Potential Clinical Applications Of Ehd2mentioning
confidence: 99%